Pemberdayaan UMKM Komunitas Preman Super dalam Pemanfaatan Pemasaran Digital - Edwy, Ferby Mutia; Firdaus, Mohammad Iqbal (Jurnal Pengabdian dan Peningkatan Mutu Masyarakat (Janayu), 2024)
Purpose – This community service activity aims to introduce the concept of digital marketing to members of the Preman Super Community (Independent Women Sources of Change) and help MSMEs utilize digital marketing to increase competitiveness. Design/methodology/approach – Implementation of activities uses the Participatory Rural Appraisal method with four stages: identification, program design preparation, implementation, and evaluation. Findings – This activity results in an increased understanding of the Preman Super Community MSMEs regarding digital marketing. Community members realize the importance of digital marketing to increase business competitiveness and expand market share. Utilizing digital marketing can also help MSMEs to increase brand awareness. Originality/value – The era of digitalization requires MSMEs to innovate in the type of marketing they carry out. This service activity was carried out to educate the Super Preman Community MSMEs so they can utilize digital marketing to increase business competitiveness.